Our experience with spreader graft in septorhinoplasty by open approach - Tiwari, Markandeya; Kumar, Surender; Goel, H. C.; de sa, Carnegie (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Spreader graft being one of the best method for volumetric expansion of internal nasal angle to address the nasal valve pathologies, popularised by Sheen. Methods: To evaluate its functional effect on relieving nasal obstruction secondary to nasal valve pathologies, our study was conducted in 40 patients (35 male and 5 female; mean age 28 years) having both external nasal deformity and nasal obstruction. NOSE scale was used to assess functional improvement. Results: Out of total 40 patients (22 patients with saddle nose deformity, 10 crooked nose and 8 nasal dorsum deformity), 35 patients (87.5%) were fully satisfied with functional outcome as assessed by NOSE score. Conclusions: Spreader graft is good way to handle nasal obstruction secondary to narrow internal nasal angle.